Quantum Computing and Applications: Its Effects on Cybersecurity - Syed Abdul Quddus; Saad Ali Siddique; Ahtiqa Tabassum (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
The study examined final-year undergraduate business students’ perception regarding the relative importance of different employability skills for entry-level positions; the extent to which academic, personal management and teamwork skills are fully developed at the point of graduation; and the relative importance of different learning methods in aiding the acquisition of employability skills. Based on a structured survey questionnaire administered to final-year undergraduate business students, the four most important employability skills for recruitment to entry-level positions are communication skills, learning skills, positive attitudes and behaviours, and problem-solving skills. While the literature finds communication skills, problem-solving skills and interpersonal skills often appear among the highest ranked skills in terms of importance, the significance of this study is that ‘learning skills’ ranked as the second most important employability skill. In today’s fast-paced work environments that are characterised by rapid knowledge obsolescence and an unknown future, willingness to learn and proactive lifelong learning are key to sustaining long term employability. Based on students’ responses, the areas that ranked below expectation were numeracy skills, IT literacy skills, and ability to ‘resolve and manage conflicts’ within teams. The study finds that students used a combination of traditional and student-centred learning methods and pedagogies to acquire employability skills